2017
DOI: 10.22456/1983-201x.66436
|View full text |Cite
|
Sign up to set email alerts
|

A formação do regime de autonomia avaliativo no Sistema Nacional de Pós-graduação e o futuro das relações entre historiografia, ensino e experiência da história.

Abstract: Resumo: Neste artigo analiso como a acomodação da historiografia em um regime de autonomia marcado por modelos avaliativos metrificáveis afasta o campo de suas origens disciplinares no século XIX e do desenvolvimento profissional processado ao longo do século XX. Entendo por "regime de autonomia" o arranjo de forças históricas que possibilita um determinado discurso ganhar individualidade e diferenciar-se no tecido de enunciações disponíveis em época e lugar definidos. Um "regime" é a forma de descrevermos com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Resulting from this is the rising incapacity of those categories of classical modernity, such as "formation" and "development", to express the temporal dimension of these new fractured social experiences. The absence of a future figured as a project and the incessant replacement of the present can be found in categories such as the "flexibility", "efficiency", and "updating" of its own semantic network (Pereira;Araujo, 2017).…”
Section: First Movement: Historical Experience Acceleration and Newmentioning
confidence: 99%
See 1 more Smart Citation
“…Resulting from this is the rising incapacity of those categories of classical modernity, such as "formation" and "development", to express the temporal dimension of these new fractured social experiences. The absence of a future figured as a project and the incessant replacement of the present can be found in categories such as the "flexibility", "efficiency", and "updating" of its own semantic network (Pereira;Araujo, 2017).…”
Section: First Movement: Historical Experience Acceleration and Newmentioning
confidence: 99%
“…In a study focused on the field of letters, for example, Jaime Ginzburg showed the gap between the valorization of publication in the periodicals assessed as A1 by Capes and the use in citations and debates of the same periodicals. Of the 85 articles analyzed, only three citations were found (Ginzburg, 2015, p. 25;Araujo, 2017). One of the effects of this process is thus the sterile proliferation of articles (or collections) without readers, whose effects in debates are increasingly hard to note.…”
Section: -205mentioning
confidence: 99%